Factors Associated with the Decline in HIV and AIDS Prevalence Rate in Volta Region of Ghana (International Journal of Scientific Research and Management (IJSRM), 2018)
The research aims at finding out factors that contributed to the decline in HIV and AIDS prevalence rate in the Volta Region of Ghana from 2006 to 2008. Three research questions were asked to guide the review of related literature on the above–mentioned research topic.Simple random sampling was used to select 10 hospitals in the region for the study. Simple random sampling technique was used to select 250 respondents, thus 25 from each of the hospitals sampled. Questionnaire was the main instrument for data collection which consisted of 30 close ended items. The study revealed that in the opinion of 82.7% of health and medical personnel who responded to the questionnaire indicated that behaviour change contributed highly to the decline of HIV and AIDS prevalence rate in the Volta Region. Also, 84.4% and of 99.6% of the respondents agreed that specific HIV and AIDS interventions and HIV and AIDS education respectively contributed highly to the reduction in HIV prevalence rate in the Volta Region. The recommendations made were that the government and non-governmental organizations must intensify their strategies that are geared towards the behavior change of their members. They must also carry out specific intervention strategies to curb HIV and AIDS menace.